Sleep disturbance and language delay in children with attention-deficit/hyperactivity disorder: is there an association? - Omayma Afsah; Mai Bondok; Hemmat Baz (The Egyptian Journal of Otolaryngology)
Abstract Background Particularly of clinical and research interest is the connection between attention-deficit/hyperactivity disorder (ADHD) and sleep disturbances. Among children with ADHD, language delay is a frequent comorbidity. The present study aimed at examining the association between sleep disturbance and both gender and language development in children with ADHD, given the potential relationship between them. Methods A sample of 70 Arabic-speaking children with ADHD in the age range 4–9 years including 48 males and 22 females were subjected to an assessment protocol that included assessment of sleep disturbances by a parental questionnaire and language assessment by a standardized language test. Results: 57% of children with ADHD had sleep disturbance. There was significant association between the presence of sleep disturbance and the type of ADHD. Sleep disturbance was not shown to be significantly associated with either gender or language development. Conclusion: The occurrence of sleep disturbance was not significantly associated with language delay in children with ADHD of mild to moderately-severe degree and borderline to average intelligence.